Wage mobility in times of higher earnings disparities: is it easier to climd the ladder? - Iga Magda (University of Essex, Institute for Social and Economic Research (ISER), 2008)
In this paper I study the earnings mobility in Poland and in the UK. Using both transition matrices and a wage mobility index I rst document changes in the overall wage mobility in Poland across time, then compare mobility patterns among Polish and British employees. I focus in particular on low wage workers and analyze their transitions within the earnings distribution and between dierent labour market states. Finally, I demonstrate that changes in the earnings mobility in Poland do not seem to be linked to changes in the overall wage dispersion.
Keywords: 330